'Essential but not always available when needed' – an interview study of physicians' experiences and views regarding use of obstetric ultrasound in Tanzania. Issue 1 (1st December 2016) - Åhman, Annika; Kidanto, Hussein Lesio; Ngarina, Matilda; Edvardsson, Kristina; Small, Rhonda; Mogren, Ingrid
Abstract : Background: The value of obstetric ultrasound in high-income countries has been extensively explored but evidence is still lacking regarding the role of obstetric ultrasound in low-income countries. Objective: We aimed to explore experiences and views among physicians working in obstetric care in Tanzania, on the role of obstetric ultrasound in relation to clinical management. Design: A qualitative study design was applied. Data were collected in 2015, through 16 individual interviews with physicians practicing in obstetric care at hospitals in an urban setting in Tanzania. Data were analyzed using qualitative content analysis. Results: Use of obstetric ultrasound in the management of complicated pregnancy was much appreciated by participating physicians, although they expressed considerable concern about the lack of ultrasound equipment and staff able to conduct the examinations. These limitations were recognized as restricting physicians' ability to manage complications adequately during pregnancy and birth. Better availability of ultrasound was requested to improve obstetric management. Concerns were also raised regarding pregnant women's lack of knowledge and understanding of medical issues which could make counseling in relation to obstetric ultrasound difficult. Although the physicians perceived a positive attitude toward ultrasound among most pregnant women, occasionally they came across women who feared that ultrasound might harm the fetus. Conclusions: There seems to be a need to provide more physicians in antenatal care in Tanzania with ultrasound training to enable them to conduct obstetric ultrasound examinations and interpret the results themselves. Physicians also need to acquire adequate counseling skills as counseling can be especially challenging in this setting where many expectant parents have low levels of education. Providers of obstetric care and policy makers in Tanzania will need to take measures to ensure appropriate use of the scarce resources in the Tanzanian health care system and prevent the potential risk of overuse of ultrasound in pregnancy.